(3GdPjd Ydi Pjd JGQjN GdGSdGes - (3CMeO Hf YHO GdQMje Hf GdMSjf GdcQOj GdYQGbj, CHh RQYI, hdj GdOjf , GHf GdYQGbj, J (B826 (3g` s
(3ChdgG (B:s
(3EHJOCg HSfI ehdOg hgj SfI (B762(3g` s
(3BNQgG (B:s
(3GfJgi ajg Edi SfI(B786(3g` s
(3Pjd Hg Ydi cJGH CHjg GdMGaX Rjf GdOjf GdYQGbi GdPi LYdg PjdkG Ydi cJGH GdYHQ ddPgHis
(3fbdkG Yf fSNI HNW GdeDdas
(3JHUQI GdYfhGf (B:s
(3JPjjd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe JGQjN (B- (3U (B69 s
Keywords: (3GdJGQjNs